Phototoxic effect of TPPS4 and MgTPPS4 on DNA fragmentation of HeLa cells - Binder, S; Kolarova, H; Tomankova, K; Bajgar, R; Daskova, A; Mosinger, J (Toxicology in vitro, 2011)
Photodynamic therapy (PDT) is an alternative method of tumour treatment. It is based on a photochemical reaction of a photosensitizer, irradiation, and O(2) which converts to cytotoxic (1)O(2) and other forms of reactive oxygen species (ROS). The comet assay (also called single-cell gel electrophoresis, SCGE) is a sensitive, simple and quantitative technique for detection of DNA damage. In our study we investigated the phototoxicity of the two porphyrin photosensitizers, TPPS4 and MgTPPS4, on HeLa cells. Three different radiation doses and six different concentrations of the photosensitizers were used. Our results show that the DNA of the cells treated with the TPPS(4) and MgTPPS(4) at the concentrations higher than 5 μM was highly fragmented indicating a strong phototoxic effect resulting in a cell apoptosis. On the base of our results we can hypothesize that even the irradiation dose of 1 J cm(-2) is sufficient enough to provoke the DNA fragmentation.
Keywords: dávka záření; Photochemotherapy; fotosenzibilizující látky; fotochemoterapie; Comet Assay; Photosensitizing Agents; fragmentace DNA; vztah mezi dávkou a účinkem léčiva; hořčík; Magnesium; metaloporfyriny; HeLa buňky; Radiation Dosage; DNA Fragmentation; lidé; HeLa Cells; Metalloporphyrins; Humans; kometový test; Porphyrins; apoptóza; porfyriny; Dose-Response Relationship, Drug; Apoptosis